2017
DOI: 10.3390/s17102183
|View full text |Cite
|
Sign up to set email alerts
|

SFOL Pulse: A High Accuracy DME Pulse for Alternative Aircraft Position and Navigation

Abstract: In the Federal Aviation Administration’s (FAA) performance based navigation strategy announced in 2016, the FAA stated that it would retain and expand the Distance Measuring Equipment (DME) infrastructure to ensure resilient aircraft navigation capability during the event of a Global Navigation Satellite System (GNSS) outage. However, the main drawback of the DME as a GNSS back up system is that it requires a significant expansion of the current DME ground infrastructure due to its poor distance measuring accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Modeling confirmed that changing the ρ in intervals of 2 to 12 changes the potential accuracy of DME. Distance errors varied between 0.3 and −0.13 m. Work [13] deals with a high accuracy DME pulse for alternative aircraft position and navigation. The paper introduces a method to improve DME distance measuring accuracy by using a new DME pulse shape.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Modeling confirmed that changing the ρ in intervals of 2 to 12 changes the potential accuracy of DME. Distance errors varied between 0.3 and −0.13 m. Work [13] deals with a high accuracy DME pulse for alternative aircraft position and navigation. The paper introduces a method to improve DME distance measuring accuracy by using a new DME pulse shape.…”
Section: Discussionmentioning
confidence: 99%
“…The DME system has some drawbacks-including low resistance to interference [4][5][6][7][8][9][10][11][12][13][14][15]. Therefore, it is of practical importance that the task of optimizing the receiver of a DME system that operates under wide-band fluctuation interference conditions be addressed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Versions of this design have been developed that meet ICAO DME requirements while also reducing multipath induced errors. Analysis has shown it to reduce ranging errors by 36–77% .…”
Section: Mitigation Techniquesmentioning
confidence: 99%